Education On Female Student Of Ar-Rohmah Islamic Boarding Junior High School To Improving Healthy Live Behavior During Pandemic Covid-19 - Ririn Harini; Dyah Sasi Retnaning Gumilar (Universitas Muhammadiyah Malang, 2022)
Background:Learning in schools has been carried out face-to-face, but the COVID-19 pandemic is not over yet. Implementation of health protocols properly and correctly is needed to prevent transmission of the virus in the school environment. However, many students still do not understand how to wash their hands in 6 steps and use protective equipment properly. Objective: To improve a healthy lifestyle for students at SMP Ar-Rohmah Islamic Boarding School during the pandemic Covid-19. Methods: The dedication is carried out with an educational method in the form of hands-on practice on the 6 steps of hand washing and how to use protective equipment correctly. Results: After receiving education, students can apply the 6-step hand washing method and use protective equipment properly and independently. Conclusion: The education that has been carried out has enabled the female students at SMP Ar-Rohmah Islamic Boarding School to apply 6 steps of hand washing and use PPE properly and independently.